2005
DOI: 10.2337/diacare.28.7.1763
|View full text |Cite
|
Sign up to set email alerts
|

Relation of C-Reactive Protein to Insulin Resistance and Cardiovascular Risk Factors in Youth

Abstract: OBJECTIVE -Insulin resistance and C-reactive protein (CRP) levels are strongly correlated in adults. This study explored the relationship in youth.RESEARCH DESIGN AND METHODS -Associations between CRP levels, cardiovascular risk, and insulin resistance measured by the euglycemic clamp were investigated in 342 healthy Minneapolis youth.RESULTS -There was no difference in mean CRP levels among boys (n ϭ 189, CRP 1.10 Ϯ 0.46 mg/l) and girls (n ϭ 153, CRP 1.16 Ϯ 0.63 mg/l; P ϭ 0.32). There was also no difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 35 publications
10
48
0
3
Order By: Relevance
“…linking MetS components to hsCRP levels in children and adolescents (8,13,26). However, similar to other reports (29), the associations (except for SBP) disappeared after controlling for adiposity measures, suggesting that in healthy prepubertal children, the observed relationships were mediated through the obesity status. Hence, it could be hypothesized that a longer period of exposure to or accumulation of excessive fat mass may be required, or a critical degree of inflammation must be reached before the effects of hsCRP become significant.…”
Section: Discussionsupporting
confidence: 88%
“…linking MetS components to hsCRP levels in children and adolescents (8,13,26). However, similar to other reports (29), the associations (except for SBP) disappeared after controlling for adiposity measures, suggesting that in healthy prepubertal children, the observed relationships were mediated through the obesity status. Hence, it could be hypothesized that a longer period of exposure to or accumulation of excessive fat mass may be required, or a critical degree of inflammation must be reached before the effects of hsCRP become significant.…”
Section: Discussionsupporting
confidence: 88%
“…However, other investigators found that, after adjustment for adiposity in adolescents, CRP was not significantly associated with the MetS and its components. These authors suggested that the MetS may precede the development of CRP elevation (38 ). Ford et al (36 ) showed an independent association between abdominal obesity and CRP concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship with obesity is particularly well documented (14,18,(22)(23)(24)(25). Higher blood pressure and dyslipidemias are also correlated with CRP in some reports, whereas the relationship between CRP and insulin resistance in children is less clear (13,19,22,26,27 ). Our findings were also consistent with reports of CRP concentrations in children from the 1999 -2000 NHANES database, including findings that CRP is higher in girls compared with boys, in Mexican Americans compared with non-Hispanic whites, and in overweight adolescents compared with normal-weight adolescents (28 ).…”
Section: Discussionmentioning
confidence: 99%